Soft rot decay of acetylated rattan (Calamus manan) - Hamid, Norul Hisham; Hale, Mike (2012)
The resistance of acetylated rattan against soft rot and other soil inhabiting micro-organisms was compared to beech and Scots pine woods. Calamus manan grown under rubber tree canopy aged 10 and I3 years was acetylated to different levels by reaction times (0.25 to 30 hour) and was tested to soft rot decay for 32 weeks. The untreated rattan turned to dark colour and end-tapered but the acetylated rattan was still intact. Acetylated rattan aged 10 and 13 years at decay protection thresholds of 15.4 % and 16.2 % WGs (weight gain) were fully protected, as shown by both weight loss and strength criteria. The static bending properties of untreated rattan decayed by soft rot were significantly lower than acetylated rattan.